Wudhu Itu Menyenangkan “Meningkatkan Kemampuan Berwudhu Anak dengan Metode Demonstrasi” : Studi pada TK Negeri Pembina Baubau - Ardiansyah Ardiansyah; Anisa Anisa; Fulora Fulora; Rika Arif; Sastrawaty Sastrawaty; Wa Muli; Sitti Karmina; Saharia Rorano (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This study aims to explore the effectiveness of the demonstration method in improving the ablution skills of early childhood. The study was conducted at TK Negeri Pembina Baubau with a Classroom Action Research (CAR) approach consisting of two cycles. The subjects of the study were 20 early childhood students who were students at the institution. The demonstration method was used to provide direct examples of the correct stages of ablution, with the hope that children could imitate them correctly. The results of the study showed a significant increase in both ablution practice skills and children's enthusiasm during the learning process. In the second cycle, the majority of children were able to perform ablution independently with the correct sequence and movements. In addition, the learning atmosphere became more active and enjoyable. Thus, it can be concluded that the demonstration method is effective in creating a positive learning experience and is able to optimally improve the ablution skills of early childhood.